Using the Delphi Approach to Identify Priority Areas for Health Visiting Practice in an Area of Deprivation - Rosamund Bryar; Sandra Anto-Awuakye; Janice Christie; Claire Davis; Karen Plumb (Nursing Research and Practice)
Families with children living in areas of high deprivation face multiple health and social challenges, and this high level of need has impacts on the work of health practitioners working in such areas. All families in the UK with children under five years have access to health visiting services, and health visitors have a key role in mitigating the effects of deprivation by addressing health needs through evidence based practice. This paper reports the first stage of a project in Tower Hamlets, London, an area of significant deprivation, which aims to develop an evidence-based toolkit to support health visitors in their practice with families. The first stage used a modified Delphi process to identify the priority health needs of families in the area between June and July 2012. The three-stage Delphi process involved 25 people: four health visitors, four other members of the health visiting service, and 17 representatives of other services working with families. A focus group event was followed by a second event where individuals completed a questionnaire ranking the 27 priorities identified in the first event. The consultation process concluded with participants completing a second questionnaire, by email, confirming or changing their prioritisation of the topics.